"THE DEFENSE OF HONOR" UNDER DEBATE: CASES AND ARGUMENTS REGARDING THE LEGITIMATE DEFENSE OF HONOR IN JURY TRIALS - Buccini, Alexandre (Editora Impacto Científico, 2025)
This article analyzes the persistence of the so-called “legitimate defense of honor” as an argumentative strategy used in crimes of passion tried by Brazilian jury courts, despite its complete absence from the legal system. Throughout the twentieth century, this thesis was repeatedly invoked to justify homicides and attempted homicides against women, and it continued to influence judicial decisions even after the 1988 Constitution and the legal recognition of feminicide as a qualified homicide. Its persistence is rooted in patriarchal cultural values that associate male honor with control over female behavior, shifting blame from the perpetrator to the victim. This study uses qualitative and descriptive bibliographic research to examine the historical evolution of legitimate defense, its adaptation as a justification for violence against women, and its endurance within social and legal imaginaries. The findings reveal that, although extralegal, the thesis has contributed to the normalization of gender-based violence and to recurring practices of victim-blaming. In March 2021, the Federal Supreme Court prohibited its use in jury trials, recognizing its incompatibility with constitutional principles such as human dignity, equality and the right to life. This ruling is an important legal milestone; however, its effectiveness depends on social dissemination and on the broader cultural transformation needed to eliminate arguments that legitimize feminicide.DOI: https://doi.org/10.56238/edimpacto2025.084-016